Association of Dairy Intake With Body Composition and Physical Function in Older Community-Dwelling Women - Radavelli-Bagatini, S; Zhu, Kun; Lewis, Joshua; Dhaliwal, Satvinder; Prince, Richard (Elsevier, 2013)
Impaired muscle function has been demonstrated to be an important predictor of frailty and fracture in elderly people. The aim of this cross-sectional study was to evaluate the association of dairy intake with body composition and physical performance in 1,456 older women aged 70 to 85 years. Participants were assessed for dairy consumption (milk, yogurt, and cheese) by a validated food frequency questionnaire, body composition by dual-energy x-ray absorptiometry, and physical performance using hand-grip strength and Timed Up and Go tests. Data on falls in the previous 3 months were collected. Women were categorized according to tertiles of dairy intake: first tertile (≤1.5 servings/day), second tertile (1.5 to 2.2 servings/day), and third tertile (≥2.2 servings/day). Main outcomes were compared using analysis of covariance adjusting for confounding factors. Odds ratios for self-reported falls and risk of poor Timed Up and Go were obtained by using binary logistic regression. The mean age was 75.2±2.7 years and body mass index was 27.2±4.7. Compared with those in the first tertile of dairy intake, women in the third tertile had significantly greater whole body lean mass (34.4±0.3 vs 32.9±0.3 kg; P=0.001) and appendicular skeletal muscle mass (15.3±0.2 vs 14.5±0.2 kg; P=0.002), greater hand-grip strength (20.9±0.2 vs 20.0±0.2 kg; P=0.02), and 26% lower odds for a poor Timed Up and Go test (P=0.04); however, the difference in prevalence of falls in the previous 3 months was not statistically significant (10.3% vs 14.4%; P=0.08). Our results suggest an association of higher dairy intake with greater whole body lean mass and better physical performance in older women.